Perjanjian Kredit Sumut Sejahtera PT. Bank Sumut Dalam Kaitannya Dengan Penyelesaian Kredit Bermasalah - Adi Saputra; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2019)
Abstract. Micro, small and medium enterprises have so far shown their strategic role especially in expanding employment opportunities, increasing community income and economic growth in Indonesia including maintaining and recovering the economy during the critical condition. One of the difficulties experienced by the micro entrepreneurs in exanding their business is the limited cap[ital due to the difficulty of accessing the working capital provided by the banks because of the absence of collateral. It is stated in Article 3 and Article 6 of Law No.10/1998 on Banking that the main function of Indonesian banking is to raise and distribute public funds, and one of the bank businesses is to extend credit. In relation to this matter, to help develop the micro business without collaterals, Bank Sumut lunched a product called Kredit Sumut Sejahtera, a credit extended to the Kelompok Keuangan Mikro (Micro Financial Group= MFG) with 20 (twenty) till 30 (thirty) members through banking education in the form of guidance, training and consultation on the compulsory weekly meetings. This MFG applies the system of Grameen Bank popularized by Muhammad Yunus in Bangladesh. This credit extension is only to fund the micro working capital especially to empower the financially disadvantaged women. Although, up to now, there is no special regulation from Bank Indonesia on the technical implementation of credit extension through the Grameen Bank system, the bank can extend the credit through this Grameen Bank system based on Law No.10/1998 on the Amendment of Law No.7/1992 on Banking, Law No.20/2008 on Micro, Small and Medium Enterprises, the Regulation of Bank Indonesia No. 14/22/PBI/2012 on Credit Extension, or the Financing by Commercial Banks and Technical Assistance for the Development of Micro, Small and Medium Enterprises. During this credit extension activity, the incident of non-performing loan is unavoidable but it can be minimized. If this Kredit Sumut Sejahtera is not performing well due to the factors raised by the debtors, the strength of joint-liability groups is one of the effective efforts to settle the problem, and the bank can debit the debtors’ savings to pay their debt or file an application to the court in order to confiscate all of debtors’ assets for the repayment of their debt under section 1131 of the Indonesian Civil Codes. The incident of the non-performing loan can be avoided through the in-depth analysis done to the debtor before the credit is extended, doing strict monitoring system in credit extension, and making a clause in the credit agreement that can protect the bank. Keywords: Credit Agreement, Non-Collateral Credit for Micro Business, Non-Performing Loan Settlement